Maximizing Ethylene Production Yield by Modifying the Methanol to Olefin Process with the Addition of a Distillation Tower - Sitio, Arnanda R.H; Azahra, Dini Salwa; Zahrani, Fatimah Nur; Martantri, Reyna Zahwa Muji; Ajitira, Sendy Nanda (Journal of Chemical Engineering Research Progress, 2024)
Ethylene is a feedstock that produces polyethene and other industrial chemicals such as ethylene oxide. The methanol-to-olefins process is a technology designed to transform methanol into light olefins like ethylene and propylene, which are crucial raw materials in the petrochemical industry. The first reaction involves the production of dimethyl ether and water from methanol. The second reaction consists of the conversion of dimethyl ether to ethylene and water. This paper will explain how to maximize ethylene production yield by modifying the methanol to olefin process. The process modification was carried out by adding a distillation tower. Based on process modifications increased the ethylene quantity from 21,070 tons/year to 179,400 tons/year. The case study results indicate an increasing yield of the product exiting. Copyright © 2024 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).